2003
DOI: 10.1088/0266-5611/19/2/201
|View full text |Cite
|
Sign up to set email alerts
|

Separable nonlinear least squares: the variable projection method and its applications

Abstract: In this paper we review 30 years of developments and applications of the variable projection method for solving separable nonlinear least-squares problems. These are problems for which the model function is a linear combination of nonlinear functions. Taking advantage of this special structure, the method of variable projections eliminates the linear variables obtaining a somewhat more complicated function that involves only the nonlinear parameters. This procedure not only reduces the dimension of the paramet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
504
0
3

Year Published

2008
2008
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 669 publications
(509 citation statements)
references
References 111 publications
(140 reference statements)
2
504
0
3
Order By: Relevance
“…The above iterative algorithm can be viewed as a solution of a separable nonlinear least squares problem (Ruhe and Wedin, 1980; Golub and Pereyra, 2003). The parameters are separated into two sets, where { β j } are linear parameters and { α j } are nonlinear parameters.…”
Section: Nonnegative Garrote For Nonlinear Additive Modelsmentioning
confidence: 99%
See 1 more Smart Citation
“…The above iterative algorithm can be viewed as a solution of a separable nonlinear least squares problem (Ruhe and Wedin, 1980; Golub and Pereyra, 2003). The parameters are separated into two sets, where { β j } are linear parameters and { α j } are nonlinear parameters.…”
Section: Nonnegative Garrote For Nonlinear Additive Modelsmentioning
confidence: 99%
“…It has been shown that eliminating one set of parameters can result in faster convergence of the optimization problem. We refer to Ruhe and Wedin (1980) and Golub and Pereyra (2003) and references therein for detailed descriptions of separable nonlinear least squares problems and the convergence properties of related algorithms.…”
Section: Nonnegative Garrote For Nonlinear Additive Modelsmentioning
confidence: 99%
“…The form of Equation (5) is known as the variable projection functional [25] as the operator B(B T B) 21 B T is a projection operator. This form of the cost function has several advantages over the original cost function of Equation (3).…”
Section: Optimal Registration Of Aliased Images Using Variable Projecmentioning
confidence: 99%
“…While this second approach is more principled than the two-stage approach, we show that the use of cyclic coordinate descent is not the most efficient search strategy. It has been shown [25], that optimization using the coordinate descent approach is numerically less well conditioned and likely to become stuck in local minima.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation